A Comparative Study on Plant Biodiversity of Oak (quercus Semecarpifolia Smith.) and Mixed Oak-deodar (cedrus Deodara D. Don.) forests in Central Himalayan Region of Uttarakhand - Singh, Pushkar; Attri, Brij Lal; Das, Biswajit (Indian Forester, 2014)
Present study concluded that the total plant species was greater in oak-deodar mixed forest in Central Himalayan region. This type of forest recorded more trees and shrubs whereas oak dominated forest constituted higher herbs. The tree and herb density was 1700 and 92000 respectively in oak dominated forest whereas shrub density was 2356 per ha. The A/F ratio of trees and shrubs was 0.363 and 1.39 in the mixed forest as compared to 0.023 and 0.89 in oak dominated forest. Further, A/F ratio of herbs was 1.45 in the latter to that of 0.6 in the former. The total cover (%) of shrubs was 5.23 and 6.18 whereas for herbs it was recorded as 13.46 and 10.29 in oak dominated and mixed oak-deodar forest respectively. The diversity of trees and shrubs was better in mixed oak-deodar forest whereas for herbs it was higher in oak dominated forest. The assessment of the plant biodiversity in different forests revealed that various disturbances do not provide time for the ecosystem recovery and widen the forest gap and fragmentation of the land in the region.